2018
DOI: 10.1016/j.redox.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in GSH:GSSG activate vascular endothelial growth factor receptor 2 (VEGFR2) in human aortic endothelial cells

Abstract: The angiogenic capacity of local tissue critically regulates the response to ischemic injury. Elevated reactive oxygen species production, commonly associated with ischemic injury, has been shown to promote phosphorylation of the vascular endothelial growth factor receptor 2 (VEGFR2), a critical regulator of angiogenesis. Previous data from our lab demonstrated that diminished levels of the antioxidant glutathione positively augment ischemic angiogenesis. Here, we sought to determine the relationship between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Catalase in the mitochondrial matrix can also convert H 2 O 2 into water and molecular oxygen [86,87]. Glutathione biosynthesis is catalyzed by glutathione reductase using the oxidation of reduced nicotinamide adenine dinucleotide phosphate (NADPH) into NADP and is crucial in antioxidant activities in the mitochondria [88,89] Another important source of ROS in the re-perfused heart are the two isoforms of monoamine oxidases (MAO), MAO-A and MAO-B, which are located on the outer mitochondrial membrane [92]. It has been demonstrated that MAO-A activity is enhanced by I/R injury and is responsible for the precipitation of hydrogen peroxide and the progression towards left ventricle hypertrophy and cardiac remodeling [93].…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Catalase in the mitochondrial matrix can also convert H 2 O 2 into water and molecular oxygen [86,87]. Glutathione biosynthesis is catalyzed by glutathione reductase using the oxidation of reduced nicotinamide adenine dinucleotide phosphate (NADPH) into NADP and is crucial in antioxidant activities in the mitochondria [88,89] Another important source of ROS in the re-perfused heart are the two isoforms of monoamine oxidases (MAO), MAO-A and MAO-B, which are located on the outer mitochondrial membrane [92]. It has been demonstrated that MAO-A activity is enhanced by I/R injury and is responsible for the precipitation of hydrogen peroxide and the progression towards left ventricle hypertrophy and cardiac remodeling [93].…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Both lipofectamine and DMSNs‐PEI treated cells exhibited a 2.1‐fold and 1.9‐fold increase, respectively in transfection efficacy in BSO pretreated cells compared to the untreated group (Supporting Information, Figure S11B), indicating that the mRNA transfection activity benefits from the proposed GSH regulation strategy. Since BSO only blocks the synthesis of gamma‐glutamylcysteine synthetase, a rate‐limiting enzyme in GSH biosynthesis to decrease GSH level, but could not oxidize GSH to GSSG, the enhancement in mRNA transfection efficacy is not comparable with DMONs‐PEI where the reducible tetrasulfide motif contributes to GSH depletion via oxidation for upregulated mRNA transfection (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…The brain maintains a high ratio of GSH/GSSG for antioxidant defence. Depletion of all the total glutathione and a decreased GSH/GSSG ratio are the markers for oxidative stress in ischemic brain and as long as 72 hrs may be required to restore concentrations to normal values by an ischemia insult 18,19 .…”
Section: The Superoxide Dismutase and Their Mimeticmentioning
confidence: 99%